Т.ҚАЙЫПБЕРГЕНОВТЫҢ «О ДҮНЬЯДАҒЫ АТАМА ХАТЛАР» ЭССЕСИНИҢ ЖАНРЛЫҚ ӨЗГЕШЕЛИГИ ҲӘМ КОМПОЗИЦИЯСЫ - Досымбетова, А.А. (FAN va JAMIYAT, 2017)
The article is devoted to genre peculiarities and composition of the essay by T.Kaipbergenov «Letters to grandfather to another world». The importance of the character and personal opinion of the author were revealed in this essay. The importance of scientifical assumption was learned in order to expose the ecological problems. There have been analyzed the genre peculiarities of artistic functions of folklore- legends and the role of hero’s monologues in the work.